TINJAUAN YURIDIS TERHADAP PENCABUTAN HAK POLITIK BAGI TERPIDANA KORUPSI DI INDONESIA - MUHAROSA, HALIVA; Indra, Mexsasai; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In Indonesia, corruption has been increasingly practiced and even spread into all aspects of life either at the local or central levels. Corruption is called a crime for humanity because its practice has resulted in people’s poverty and suffering. During habibie’s administration, the attempt to fight corruption had been realized in the juridicial framework trought the issuance of Law No. 31/1999 on Eliminating Corruption Criminal Act replacing Law No. 3/ 1971 on Eliminating Corruption Criminal Act and then it was replaced again with Law No.20/2001 on the amendment of Law No. 31/1999 on Eliminating Corruption Criminal Act.This paper raised several issues relating to Overview Juridical against Revocation Political Rights for Convicted of Corruption in Indonesia, which is about the urgency Revocation Political Rights Against Convicted of Corruption in combating Corruption in Indonesia, and Application of Criminal Supplementary Revocation Political Rights in efforts to combat criminal offenses Corruption in Indonesia. The method used in this research is normative. Normative research method is also known as doctrinal research is a study to analyze the good law is written in the book, as well as law decided by the judge through court proceedings.Overview Juridical Against Against Revocation Political Rights for Convicted of Corruption in Indonesia in efforts to combat Corruption in Indonesia, is still considered very important penjatuhannya against perpetrators of Corruption Act, the enactment of the Criminal Supplementary Revocation Political Rights is basically aimed to scare - scare and provide a deterrent effect against corruption, so that people - those who had intended to corruption be afraid to do so, especially when considering that Indonesia is the most corrupt countries in the world, the application of the criminal had to be firm, but remains selective and liver - liver. The right to vote and be elected to public office is one part of human rights, remove, eliminate or negate the rights of citizens as a whole even though through the verdict is a violation of human rights.Key Words: Corruption, Criminal Supplementary Revocation Political Rights, Human rights.